Optimization of the geometrical parameters of bonded composite wrap for repairing cracked pipelines (Fracture and Structural Integrity, 2018)
In this study the finite element method is used to analyze the performances of bonded composite wrap repair of  cracked steel pipelines. Parametric analysis was performed in order to highlight the effects of the geometrical properties on the repair efficiency. The experimental design method is used to explore the effects of wrap dimensions (length, angle and thickness) in order to optimize  the repair process. We showed in using the MOODE.5 software the most dominant geometrical parameters on  stress intensity factor at the crack front which  to determine the most important parameters on the repair efficiency. This  optimization  can help the composite wrap designers to improve the repair performance and rehabilitation.
Keywords: Fracture mechanics; Crack; Composite; Wrap; Pipelines